Constructivism’s Relevance to The United Kingdom As A Global Climate Leader: A Case Study Of Climate Change Issue As UK’s Foreign Priority In 2021 - Irma Indrayani; Dinar Iftinan (Universitas Sultan Ageng Tirtayasa, 2022)
The UK government has been proclaiming its position as a global leader on climate change for several years. While the origins of this claim can be traced back to Margaret Thatcher's time, it has gained traction in the years since the 2015 Paris Agreement. The declaration of the UK's position as global climate leader became stronger in 2021, coinciding with the 2021 United Nations Climate Change Conference, which the UK was appointed to host. Though the event has occurred, the UK has set ambitious goals for international agreements and firmly positions itself as the leader of the movement among all other countries. This declaration is also mentioned in the UKEF Climate Change Strategy and the Net Zero movement. Based on these, this article seeks to investigate the United Kingdom's climate change strategy and efforts to cement their position as a global climate leader, as reflected primarily in their policies in 2021.